The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/01691864.2014.952337
|View full text |Cite
|
Sign up to set email alerts
|

Hand shape classification in various pronation angles using a wearable wrist contour sensor

Abstract: Hand gestures are potentially useful for communications between humans and between a human and a machine. However, existing methods entail several problems for practical use. We have proposed an approach to hand shape recognition based on wrist contour measurement. Especially in this paper, two assignments are addressed. First is the development of a new sensing device in which all elements are installed in a wrist-watch-type device. Second is the development of a new hand shape classifier that can accommodate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…The study of the forearm pronation/supination motions based on a photoreflector [13] for assessing the forearm pronation motion effect on the measurement device, and it was revealed that the hand postures can be identified by referring to the wrist shape even with the forearm in pronation motion. Thus, for the purpose of measuring hand motions without restricting the user's actions, the effects of forearm and wrist motions on the measurement device have to be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the forearm pronation/supination motions based on a photoreflector [13] for assessing the forearm pronation motion effect on the measurement device, and it was revealed that the hand postures can be identified by referring to the wrist shape even with the forearm in pronation motion. Thus, for the purpose of measuring hand motions without restricting the user's actions, the effects of forearm and wrist motions on the measurement device have to be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is necessary to examine the wrist deformation due to the forearm pronation/supination motions and forearm angle. The study of the forearm pronation/supination motions based on a photoreflector [13] for assessing the forearm pronation motion effect on the measurement device, and it was revealed that the hand postures can be identified by referring to the wrist shape even with the forearm in pronation motion. In addition, the measurement device used in the proposed method is attached to the wrist in stable contact state, and it is thin and smallsized which is robust against the gravitational force and the like.…”
Section: Discussionmentioning
confidence: 99%
“…Pirkl et al [20] described the design and implementation of a cheap, low power, and easily wearable system for tracking the relative position and orientation of body parts by utilizing magnetic field technology. Fukui et al [12] proposed an approach to hand shape recognition based on wrist contour measurement. Sato et al [23] proposed Swept Frequency Capacitive Sensing technique that can not only detect a touch event but also recognize complex configurations of the human hands and body.…”
Section: Gesture Recognition Methodsmentioning
confidence: 99%
“…HMM-based techniques may also not be suitable for hard real-time (synchronized clock-based) systems due to its latency [5]. Since data sets are not necessarily large enough for training, Support Vector Machine (SVM) is a classical alternative method [6][7][8]. SVM is, nevertheless, very sensitive to the selection of its kernel type and parameters related to the latter.…”
Section: Introductionmentioning
confidence: 99%